PENGARUH HARGA, INFLASI, DAN PRODUKSI TERHADAP VOLUME EKSPOR BUTSUDAN PADA PT. MARUKI INTERNASIONAL INDONESIA MAKASSAR - Faizal Rizal Zainal (Jurnal Bisnis dan Kewirausahaan, 2019)
The aim of this study was to measure influence of prices, inflation, and production had on the volume of export Butsudan at PT Maruki International Indonesia Makassar partially or simultaneously. The analytical method used in this study is multiple regression analysis, T test, and F test. Results of multiple linear regression analysis show that partially the price, inflation and production have a positive and significant effect on the volume of exports Butsudan at PT. Maruki Internasional Indonesia Makassar. And also simultaneously result indicate that price, inflation and production have a positive and significant effect on the volume of exports Butsudan at PT. Maruki Internasional Indonesia Makassar.